Exploring the role of inter-municipal cooperation for promoting water circular economy: insights from a Southern European country - Riazi, F.; Fidelis, T.; Teles, F. (IWA Publishing, 2025)
This article analyses the role of inter-municipal cooperation (IMC) as a governance model in promoting water circular economy (WCE) and water reuse practices. Despite the potential benefits offered by IMC, little is known about how could contribute to fostering WCE adoption. The article develops and uses a framework to assess the role of IMC in advancing WCE strategies, addressing three key dimensions: involvement of IMC in advancing WCE, robust governance for WCE, and territorial fit and spatial concerns. It uses Portugal as a case study within the South European Union, where water scarcity and interest in IMC approaches are growing. Considering the emphasis on collaboration in legal and legislative frameworks, the results show the constrained role of inter-municipal communities in promoting the WCE through water reuse in Portugal. In addition, the limited integration of water reuse into territorial strategies highlights the lack of integration of water management and spatial planning. Moreover, the robustness of governance is hindered by a lack of funding, inadequate infrastructure, spatial barriers, a lack of experts or knowledge, and a deficiency in common goals or diversity of interests. Further research is essential to address territorial fit and spatial considerations critical to WCE adoption.